2002
DOI: 10.1523/jneurosci.22-03-01114.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neurons of the Central Complex of the LocustSchistocerca gregariaare Sensitive to Polarized Light

Abstract: The central complex is a topographically ordered neuropil structure in the center of the insect brain. It consists of three major subdivisions, the upper and lower divisions of the central body and the protocerebral bridge. To further characterize the role of this brain structure, we have recorded the responses of identified neurons of the central complex of the desert locust Schistocerca gregaria to visual stimuli. We report that particular types of central complex interneurons are sensitive to polarized ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(188 citation statements)
references
References 41 publications
7
179
0
Order By: Relevance
“…In the desert locust, a variety of neurons of the central complex is sensitive to dorsally presented polarized light, suggesting a key role of this brain area in sky compass orientation (Vitzthum et al, 2002;Homberg, 2004;Heinze and Homberg, 2007). In the present study we have characterized additional elements of the polarization vision network in the central complex.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the desert locust, a variety of neurons of the central complex is sensitive to dorsally presented polarized light, suggesting a key role of this brain area in sky compass orientation (Vitzthum et al, 2002;Homberg, 2004;Heinze and Homberg, 2007). In the present study we have characterized additional elements of the polarization vision network in the central complex.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, we identified neurons that are suited to relay polarization vision information to descending pathways. When these data are combined with previously described cell types (Vitzthum et al, 2002;Heinze and Homberg, 2007), a general connectivity scheme of the polarization coding network in the locust central complex emerges (Fig. 10).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We thus believe that this bi-lobed major AOTu compartment serves similar spatial processing functions in honeybees and locusts. The central body of insects presumably participates in polarized light coding, visual pattern recognition, spatial orientation, right-left maneuvering, and motor control (Strauss, 2002;Vitzthum et al, 2002;Liu et al, 2006;Wang et al, 2008). The AOTu output neurons may indirectly (via the LAL) provide the central body with the spatial information necessary for these tasks.…”
Section: Aotu Function In a Physiological And Behavioral Contextmentioning
confidence: 99%
“…At the neuronal level, polarization vision pathways in the brain have been studied most extensively in locusts and crickets (Labhart and Meyer, 2002;Homberg, 2004). In these insects, the central complex is a major processing stage for polarized light (Vitzthum et al, 2002;Homberg, 2007, 2009;Sakura et al, 2008;). showed that polarization-sensitive (POL-) neurons connect the central complex to the lateral accessory lobes and the posterior protocerebrum, brain areas that are innervated by intersegmental neurons (Williams, 1975;Strausfeld and Seyan, 1985;Okada et al, 2003).…”
Section: Introductionmentioning
confidence: 99%